A critical review of the research on Translation Psychology: Theoretical and methodological approaches - Zhu, Lin (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translation Psychology, as an umbrella concept, is heterogeneous and can be investigated from different perspectives. The past few decades have witnessed the development of the cognitive–psychological approach, the social–psychological approach, the gestalt–psychological approach, and the embodied cognitive approach. These interdisciplinary approaches have spawned theoretical advances and methodological innovation, and also substantial research findings in Translation Psychology, although there are some aspects awaiting improvements. This article offers a panoramic theoretical and methodological review of these approaches: it presents their achievements, discusses the problems in their theoretical development and foresees the prospect of more integrated research on translation psychology. Multidimensional research projects on translation psychology are expected, with broader coverage of more factors influencing the translator’s psychology and more holistic views of translators in their authentic, personally, socio-culturally and historically embedded environments and networks.